Plant Glycine-Rich Proteins in Stress Response: An Emerging, Still Prospective Story - Czolpinska, Magdalena; Rurek, Michal (Frontiers in Plant Science, 2018)
Seed plants are sessile organisms which have developed a plethora of stress-sensing, responding and avoiding strategies acting on distinct structural and functional levels. Within plant cells, a number of proteins - including the glycine-rich protein (GRP) superfamily - assist in stress response and signaling. GRPs are characterized by the high content of glycine and the presence of a number of conserved segments, glycine-containing structural motifs composed of repetitive amino-acid residues. The general structure of this superfamily makes it possible to divide them into five main subclasses. Even though the participation of GRPs in the stress response was confirmed among numerous model- and non-model plant species, still little is known about any key physiological and molecular mechanisms in which those proteins are engaged. Members of class I, II and IV are involved in hormone signaling, stress acclimation, floral development and are crucial for the regulation of plant cells growth. GRPs of class IV are involved in alternative splicing or regulation of transcription and stomatal movement, seed, pollen and stamen development; their accumulation is regulated also by circadian clock. Owing to the fact that overexpression of GRPs often leads to the appearance of stress tolerance (e.g. some of them are involved in cold acclimation and in that way they may improve plant growth at low temperatures), those proteins emerge playing a promising role in agriculture through their potential engineering by means of plant genetic engineering. In general, the isolation, cloning, characterization and functional validation of the novel GRPs expressed in response to the various stress conditions might be prospective in the forthcoming years.